Bis(tert‐butylpyrene) Nanotweezers and Nanocalipers: Enhanced Extraction and Recognition Abilities for Single‐Walled Carbon Nanotubes. Issue 48 (7th November 2013) - Liu, Gang; Rahman, A. F. M. Mustafizur; Chaunchaiyakul, Songpol; Kimura, Takahide; Kuwahara, Yuji; Komatsu, Naoki
Abstract We developed a host–guest methodology for separation of single‐walled carbon nanotubes (SWNTs) according to the handedness, diameter and metallicity by the use of diporphyrin nanotweezers and nanocalipers. Although the pyrene has been frequently used to replace porphyrin, due to a similar affinity to the surface of SWNTs and better availability, the extraction and recognition abilities of dipyrene nanotweezers were not so good as those of diporphyrin ones as we reported previously. However, introduction of a tert‐butyl substituent at the 7′‐position of 2‐pyrene is found to enhance the extraction and recognition abilities of dipyrene nanotweezers and nanocalipers. That is, (6, 5)‐SWNTs were obtained in high purity by use of bis(tert‐butylpyrene) nanotweezers with a phenanthrene spacer and metallic SWNTs were highly enriched by use of bis(tert‐butylpyrene) nanocalipers with a carbazole–anthracene–carbazole spacer.